Supergene manganese ore records 75 Myr-long Campanian to Pleistocene geodynamic evolution and weathering history of the Central African Great Lakes Region – Tectonics drives, climate assists - (:unkn) unknown (My University, 2020)
The southeastern part of the Democratic Republic of the Congo locally hosts Proterozoic manganese deposits. The deposits of Kisenge-Kamata are the most significant, but manganese ores are also known to occur at Kasekelesa (former Katanga Province) and Mwene-Ditu (former Kasai Province). For the present study, cryptomelane-rich samples from these two localities were dated, using the 40Ar/39Ar step-heating method with a CO2 laser probe. The ages obtained are within a range of c. 77 Myr to c. 2 Myr. Cryptomelane formation took place at c. 76.4 Ma, c. 59.6 Ma, c. 45 Ma, c. 35 Ma, c. 23.8 Ma, c. 15.4 Ma, and c. 13.3 Ma at Kasekelesa, and it occurred at c. 35 Ma, c. 22.4 Ma, c. 15 Ma, c. 5.5–7.2 Ma, c. 3.6 Ma, and c. 2.1–2.3 Ma at Mwene-Ditu. The Campanian age (c. 76.4 Ma) recorded at Kasekelesa is the oldest 40Ar/39Ar age that has up to now been recorded for Mn ores from Africa. It documents the formation of oxidized ore along a Campanian or older erosion surface, which could be part of the ‘African Erosion Surface’. The complete age record suggests that continent-wide tectonics accounts for most of the recognized supergene ore formation episodes, controlled by vertical lithospheric movements that are ultimately responsible for alternating stages of landscape stability and erosion. Tectonics is thus regarded as the first-order control for secondary ore formation in Central Africa, over the last 80 Myr. Climate is a second-order control, because sufficient water supply is needed for supergene enrichment, whereby climatic conditions are recognized to have been favourable during some relatively cold Late Mesozoic and Paleogene periods, as well as during some humid and warm Neogene stages.
Keywords: African Research